When “mountains” come to town: Alpine Facilities in Denmark 1941-2018 - Jensen, Christian Tolstrup (Idrott, historia och samhälle, 2026)
The historical development of facilities for alpine skiing in Denmark and their relation to nature can be divided into three phases. In all phases, nature in various forms has served as an important foundation for the facilities’ seductive appeal. In the first phase, 1940-1970, the facilities were based on what unaltered nature could offer and the relation to nature unquestioned. During this period skiing as a social activity in nature was established, which continued as a foundation in the second phase from the 1970s to the 1980s. However in this second phase, a new interest in alpine skiing spurred by the ski tourism also led to construction of several hills with lifts in Denmark. The impacts of humans became obvious, but the hill’s resemblance to real alpine nature also made even the Danish hills seductive. As the winters became warmer in 1990s, alpine facilities became artificial constructions, whose connection to nature stakeholders were nevertheless eager to preserve. The study thus on the one hand confirms the importance of nature for alpine skiing prevalent in previous research on alpine skiing in e.g. Sweden and Switzerland but also that it is possible to construct a version of this nature.